Transforming Students' Paradigms Regarding Research through Experiential Learning in Entrepreneurial Accounting - Gde Deny Larasdiputra; Ni Putu Riski Martini (PT Keberlanjutan Strategis Indonesia, 2026)
This study aims to explore the shift in students' paradigms regarding research through an entrepreneurial accounting learning approach based on practical experience with an MSME. Students often perceive research or the undergraduate thesis as a rigid administrative obligation detached from real-world realities. Employing a qualitative approach with an explorative-reflective design, this study utilized